Personal Persistence and Post-Mortem Survival - Harriet E. Baber (TheoLogica, 2024)
Can a materialist look for the resurrection of the dead and the life of the world to come? Dean Zimmerman’s Falling Elevator Model is a speculative account of how persons, understood as material beings, might survive in a post-mortem resurrected state—a just-so story. It assumes endurantism, the doctrine that persons and other ordinary objects are three-dimensional beings which are wholly present at every time they exist. I argue that neither endurantism, nor purdurantism, according to which persons are four-dimensional ‘worms’ who have proper temporal parts at every time that they exist, provides a plausible account of personal survival. If you want to be a Christian materialist you should embrace exdurantism, the ‘stage theory’, according which persons are instantaneous stages and are not identical to their temporal successors either in this world or in any world to come. Exdurantism provides a plausible account of survival in ordinary cases and extraordinary cases of this-worldly fission, and of post-mortem survival.